The Volatility of 10-Year Government Bonds in the Period of Increased Economic Uncertainty - Sadowska, Maria (Metody Ilościowe w Badaniach Ekonomicznych, 2023)
Within the scope of this paper is to investigate the dynamic correlation and the volatility of 10-year sovereign bond yields in the G7 countries from January 4, 2010 to December 30, 2022. The following analyses were performed by dividing the said period into two sub-periods taking August 2, 2019 as a breaking point. Conclusions were made based on built VAR models. Conducted research indicates the USA as having the most significant influence on the rest of countries. European countries are perceived as more vulnerable to the external impact in shaping their bond yields. There are noticeable changes taking place in Italy between analyzed two periods – quotes become more dependent on other countries over time.